In vitro antifungal activity of Candida culture extracts against Trichophyton rubrum and Trichophyton mentagrophytes - Lemes, Thiago Henrique; Torrezan, Guilherme Silva; Polaquini, Carlos Roberto; Regasini, Luis Octavio; Almeida, Bianca Gottardo de; Brizzotti-Mazuchi, Natália Seron; Ribeiro, Mariela Domiciano; Maschio-Lima, Taiza; Caetano, Maicon Henrique; Pattini, Veridianna Camilo; Paziani, Mario Henrique; von Zeska Kress, Marcia Regina; et al. (Brazilian Journal of Case Reports, 2021)
Onychomycoses are nail infections caused primarily by dermatophytes fungi, yeasts, and other filamentous fungi, characterized by persistent infections, prolonged therapy, and high recurrence rates. In clinical practice, some of these occurrences present two or more microorganisms, and the interactions among them can change the chemical environment mediated by small diffusible molecules, producing a competitive niche. The aim of this study was to evaluate the antifungal activity of individual extracts of pure cultures of Candida albicans and C. parapsilosis against dermatophytes. To obtain the fungal extracts, cultures were filtered through a 0.2 μm membrane and submitted to liquid-liquid extraction using ethyl acetate. The Minimal Inhibitory Concentration (MIC) of each extract was evaluated by broth microdilution method and checkerboard assay with fluconazole against clinical isolates of Trichophyton rubrum and T. mentagrophytes. The invertebrate model of Galleria mellonella was used to evaluate the toxicity of the extracts. As results, the extracts of C. albicans and C. parapsilosis showed antifungal activity with MICs between 31,2 – 2000 μg/mL. In association with fluconazole, synergistic effect was detected for all combinations. The extracts presented low toxicity in G. mellonella. In the future, isolation and identification of the extract compounds may allow new therapeutic approaches in the control of fungal infections.